Anxiety in Facing the World of Work in Terms of Career Self-Efficacy and Adversity Quotient in Final Year Students - Sindi Nursalam; Dede Rahmat Hidayat; Eka Wahyuni (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Final-year students often experience anxiety when facing the transition to the workforce due to various challenges, including career uncertainty and inadequate preparation. This study aims to examine the influence of career decision-making self-efficacy and adversity quotient on anxiety in facing the world of work among final-year students. A quantitative approach with a survey method was employed. The population comprised 2,024 final-year students from the Faculty of Education at the State University of Jakarta, and a sample of 334 students was selected using quota sampling. Data were collected using three validated psychological scales and analyzed with multiple linear regression in SPSS version 27. The results indicate that career decision-making self-efficacy and adversity quotient simultaneously have a significant influence on work-related anxiety (F = 769.856, p < 0.001). Partially, career decision-making self-efficacy showed a dominant effect (t = 36.418, p < 0.001), while adversity quotient also demonstrated a significant but smaller contribution (t = 2.469, p = 0.014). The coefficient of determination (R² = 0.823) reveals that both variables collectively explain 82.3% of the variance in work-related anxiety. These findings suggest that students with higher career decision-making self-efficacy and adversity intelligence tend to experience more manageable levels of anxiety when preparing to enter the workforce. This study contributes to guidance and counseling by emphasizing the need to develop self-efficacy and adversity quotient through targeted interventions. Future research is encouraged to explore additional variables and broader populations. Keywords: adversity intelligence, anxiety in facing the world of work, self-efficacy in career decision-making